Fuzzy-logic based NSR DBA for upstream GPON - Mahmud Y.A.; Radzi N.A.M.; Abdullah F.; Din N.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Bandwidth; Computer circuits; Passive optical networks; Quality of service; Band-width utilization; Bandwidth demand; Dynamic bandwidth; Gigabit passive optical network; Fuzzy logic